LRRK2 interacts with the vacuolar-type H+-ATPase pump a1 subunit to regulate lysosomal function - Wallings, R; Connor-Robson, N; Wade-Martins, R (Oxford University Press, 2019)
Lysosomal dysfunction lies at the centre of the cellular mechanisms underlying Parkinson's disease although the precise underlying mechanisms remain unknown. We investigated the role of leucine rich repeat kinase 2 (LRRK2) on lysosome biology and the autophagy pathway in primary neurons expressing the human LRRK2-G2019S or LRKK2-R1441C mutant, or the human wild-type (hWT-LRRK2) genomic locus. The expression of LRRK2-G2019S or hWT-LRRK2 inhibited autophagosome production, whereas LRRK2-R1441C induced a decrease in autophagosome/lysosome fusion and increased lysosomal pH. In vivo data from the cortex and substantia nigra pars compacta of aged LRRK2 transgenic animals revealed alterations in autophagosome puncta number reflecting those phenotypes seen in vitro. Using the two selective and potent LRRK2 kinase inhibitors, MLi-2 and PF-06447475, we demonstrated that the LRRK2-R1441C-mediated decrease in autolysosome maturation is not dependent on LRRK2 kinase activity. We showed that hWT-LRRK2 and LRRK2-G2019S bind to the a1 subunit of vATPase, which is abolished by the LRRK2-R1441C mutation, leading to a decrease in a1 protein and cellular mislocalisation. Modulation of lysosomal zinc increased vATPase a1 protein levels and rescued the LRRK2-R1441C-mediated cellular phenotypes. Our work defines a novel interaction between the LRRK2 protein and the vATPase a1 subunit and demonstrates a mode of action by which drugs may rescue lysosomal dysfunction. These results demonstrate the importance of LRRK2 in lysosomal biology, as well as the critical role of the lysosome in PD.